Perancangan Micro Hydro Power Plant Pada Curug Xyz - Reza Gumelar; Kardiman Kardiman; Oleh Oleh (Peneliti.net, 2022)
Along with the times, the need for technology is increasingly needed to support increasing human needs, including in the field of tourism, where supporting facilities are needed so that visitors feel comfortable, one of which is lighting for waterfall tours. The design of a Micro Hydro Power Plant that can be used as lighting on the waterfall path and can also be used for other things. In the design of PLTH, various components have a relationship where when the Nozzle Diameter is used, namely, 0.20 m, 0.15 m, and 0.10 m, it produces speeds of 12.5 m/s, 82.3 m/s, and 18.5. m/s while for the power generated 233.65 Kw the amount of electrical power is the diameter of the nozzle which has an impact on the speed that hits the turbine blades and also the height of the penstock has a big effect because the higher the penstock, the greater the electricity generated because the higher the penstock, the power on the shaft. is also increasing so that the discharge becomes a parameter that affects the shaft power, the greater the water discharge, the greater the shaft power.